Children with perinatally acquired HIV exhibit distinct immune responses to 4CMenB vaccine - Cotugno, N; Neri, A; Sanna, M; Santilli, V; Manno, EC; Pascucci, GR; Morrocchi, E; Amodio, D; Ruggiero, A; Ciofi Degl Atti, ML; Barneschi, I; Grappi, S; et al. (American Society for Clinical Investigation, 2024)
Children with perinatally acquired HIV (PHIV) have special vaccination needs, as they make suboptimal immune responses. Here, we evaluated safety and immunogenicity of 2 doses of 4-component group B meningococcal vaccine in antiretroviral therapy-treated children with PHIV and healthy controls (HCs). Assessments included the standard human serum bactericidal antibody (hSBA) assay and measurement of IgG titers against capsular group B Neisseria meningitidis antigens (fHbp, NHBA, NadA). The B cell compartment and vaccine-induced antigen-specific (fHbp+) B cells were investigated by flow cytometry, and gene expression was investigated by multiplexed real-time PCR. A good safety and immunogenicity profile was shown in both groups; however, PHIV demonstrated a reduced immunogenicity compared with HCs. Additionally, PHIV showed a reduced frequency of fHbp+ and an altered B cell subset distribution, with higher fHbp+ frequency in activated memory and tissue-like memory B cells. Gene expression analyses on these cells revealed distinct mechanisms between PHIV and HC seroconverters. Overall, these data suggest that PHIV presents a diverse immune signature following vaccination. The impact of such perturbation on long-term maintenance of vaccine-induced immunity should be further evaluated in vulnerable populations, such as people with PHIV.